NILAI USAHA INDUSTRI PRIMER HASIL HUTAN KAYU PADA CV SINAR JAYA DI KECAMATAN CIGUDEG KABUPATEN BOGOR - Pradipta, Gayuh Angga; Susdiyanti, Tun; Supriono, Bambang (Jurnal Nusa Sylva, 2021)
Community forests are the source of raw materials for the Primary Wood Forest Products Industry at CV Sinar Jaya in Cigudeg District, Bogor Regency. Optimizing the use of these raw materials can affect the business value of the wood processing industry. The purpose of this study was to determine the yield value and to analyze the business value of sawmill activities at CV. Sinar Jaya. The research method was carried out by means of quantitative analysis methods of collecting production data by direct measurement and interviews as well as calculating the value of economic income obtained from sawmill activities and overall waste utilization, the size of wood raw materials includes 10 centimeters to 30 centimeters with a length of 2 ,8 meters to 3 meters. The results showed that the average yield value is 55%, productivity is 1.51 m3/hour round wood, sawn wood is 0.83 m3/hour production cost is Rp 1,181,600,000.0/year, Income value is Rp. 1,509,600,0000.00/year, net profit value is Rp. 328,000.00/year, the value of marketing costs is Rp. 0 the value of the benefit cost ratio is 1.28/year and the work performance value of logs is Rp. 12,712.89 sawn wood Rp. 22,867.14. To increase the yield, the skills of the sawing workforce must be improved to minimize damage toeach sortimen. In order for business value to increase, productivity must be intensified and the availability of raw materials must be sustainable.Â